Identifying the unlikely suspect: A massive patellar metastasis from esophageal squamous cell carcinoma—A case report - Nouman Aziz, MD; Waseem Nabi, MD; Sukhrob Makhkamov, DO; Rana Uzair Ahmad, MD; Maryam Inam Zaroo, MBBS; Seoyoon Lee, MD (Radiology Case Reports)
Esophageal squamous cell carcinoma ranks as the eighth most common global cancer, known for its aggressive metastatic potential. This report presents a rare case of a 67-year-old male with a history of cervical esophagus SCC, who developed an unusual metastasis to the patella, a site exceedingly rare for metastasis. The patient, with a history of localized spread and various treatments, presented with leukocytosis, anemia, and progressively worsening right knee pain. MRI findings revealed a significant mass at the patella's upper pole, indicative of metastatic involvement, leading to successful surgical intervention at a specialized facility. This case underscores the importance of considering atypical metastatic sites in patients with known ESCC, highlighting the complexity of managing such rare metastatic presentations and the necessity for a tailored, multidisciplinary approach in diagnosis and treatment.